Efficiency comparison of natural coagulants (Cactus pads and Moringa seeds) for treating textile wastewater (in the case of Kombolcha textile industry) - Getahun Demeke Worku; Shimeles Nigussie Abate (Heliyon)
The issue of water contamination has gotten worse worldwide due to industrialization and population increase. The wastewater discharge techniques used by Ethiopia's textile sector do not comply with the national discharge standard. Because the discharge of inadequately treated or untreated textile effluent into the environment is becoming more frequent. Thus, minimizing this trend's harm to the environment requires using the best wastewater treatment technology. Coagulation is considered one of the most effective methods for treating textile wastewaters, which technically need to have a natural or artificial coagulant added to eliminate dangerous pollutants. Nonetheless, criticism has been leveled against the use of chemical coagulants due to their serious disadvantages. This has led to an interest in substituting natural materials for chemical coagulants. The main objective of this study was to evaluate and compare the effectiveness of various powders and Moringa seed cactus pad powders when employed as a natural coagulant to clean up textile effluent. Moringa seeds and cactus pad consist of proteins (cationic and dimeric) which help in neutralizing and absorbing colloidal charges in water containing suspended solids. To examine the impacts of various operating parameters, including coagulant dose, pH, and mixing time, as well as the ideal coagulation conditions, experiments were conducted using a jar testing system. The ideal parameters were pH 4, 5 g/l of coagulant, 40 min of mixing time, 2 min of fast mixing at 100 rpm, 40 min of gradual mixing at 40 rpm, and 30 min of settling time. Under these ideal circumstances, 82.33 Moreover, cactus pad powder reduced turbidity by 53.16 %, TDS by 97 %, BOD by 58.75 %, COD by 25.37 %, Conductivity by 60 %, and TSS by 56.33 %. Therefore, using Cactus pad as a natural coagulant is advised. Rather than using Moringa seed, it efficiently eliminates turbidity, TDS, and TSS from wastewater effluents from the textile sector. Eventually, one of the natural coagulants employed in the coagulation process, Cactus pad, proved to be useful and was chosen.